Facilitators and barriers of wet nursing: a qualitative study with implications for emergencies - Abdelrahmman, Khadija; Borg, Bindi; Gribble, Karleen; Mihrshahi, Seema (Frontiers in Nutrition, 2025)
IntroductionSupporting recommended breastfeeding practices, including wet nursing in emergencies, is crucial to providing safe and nutritious food for infants and young children to support their health and wellbeing in critical resourced situations. However, it is only now that practical guidelines for implementing wet nursing in emergencies are being developed (by UNICEF). As there is very little literature on wet nursing in contemporary settings, this study aimed to explore current wet nursing experiences to identify the facilitators and barriers of the practice, especially in emergencies.MethodsOnline semi-structured interviews were conducted from September to November 2023 with eight breastfeeding counselors and advocates. Transcripts were inductively analyzed using a reflexive thematic approach.ResultsSeven themes were identified that reflect the factors affecting wet nursing. These included “wet nursing saved lives,” “breastfeeding is valued,” “infant formula is normalized,” “risk of infection transmission,” “all stakeholders' acceptance,” “counseling approach,” and “planning for implementation.” These results suggest that facilitators and barriers that generally affect maternal breastfeeding in emergencies also influence wet nursing. Certain obstacles may have a particular impact on wet nursing, including the risk of infection transmission, negative attitudes toward wet nursing and the need for culturally sensitive counseling to mediate wet nursing.ConclusionPromoting wet nursing is an Infant and Young Children Feeding in Emergencies recommendation (IYCF-E) for non-breastfed infants. Implementing wet nursing programs can be in line with supporting good breastfeeding practices in emergencies. The results of this study can guide practical steps for implementing wet nursing and future investigation in different contexts.